Application of a transport organisation model based on Transit-Oriented Development: A case study of urban railway line No. 1 in Ho Chi Minh city, Vietnam - Phu Quang Tran, Quoc An Bui; Thai Hong Nguyen (Vietnam Journal of Science, Technology and Engineering, 2026)
Metro line No. 1 is the first urban railway line in Ho Chi Minh city, traversing densely populated urban areas and major passenger attraction centres. While it offers the potential for modern transport connectivity, operational experience has revealed that the existing transport infrastructure in adjacent areas does not fully meet passenger travel demand and has not kept pace with the city’s rapid urban development. This study focuses on assessing the scientific basis and current state of transport organisation, with the aim of applying the Transit-Oriented Development (TOD) model to Metro line No. 1. The research develops and compares two simulation scenarios: (i) the current situation scenario, reflecting existing conditions of transport connectivity, and (ii) the TOD scenario, applying TOD-based transport organisation solutions. Transport network performance indicators analysed from the simulation results include travel time, level of service, accessibility, and traffic volume. Based on the analysis of current conditions, the study proposes solutions and evaluates their effectiveness through simulation results to formulate a set of TOD-based transport organisation measures. These proposals are expected to enhance the operational efficiency of Metro line No. 1 while promoting the sustainable development of Ho Chi Minh city’s urban areas.